2019
DOI: 10.1002/cbic.201900028
|View full text |Cite
|
Sign up to set email alerts
|

Cell Profiling Based on Sugar‐Chain–Cell Binding Interaction and Its Application to Typing and Quality Verification of Cells

Abstract: Developing methods to determine cell type and cell state has been a significant challenge in the field of cancer diagnosis as well as in typing and quality verification for cultured cells. Herein, we report a cell profiling method based on binding interactions between cell‐surface sugar‐chain‐binding proteins and sugar‐chain‐immobilized fluorescent nanoparticles (SFNPs), together with a method for cell typing and cell quality verification. Binding profiles of cells against sugar chains were analyzed by perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…43,44 Our previous studies demonstrated that sugar chain immobilized fluorescent nanoparticles (SFNPs), which are immobilized with a high density of sugar chains on the surface of quantum dots, can selectively bind to cell surface sugar chain binding receptors. 45,46 In the present study, a high density of α-mannose was functionalized on the surface of GNPs, and they appear to work for targeting MR.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 Our previous studies demonstrated that sugar chain immobilized fluorescent nanoparticles (SFNPs), which are immobilized with a high density of sugar chains on the surface of quantum dots, can selectively bind to cell surface sugar chain binding receptors. 45,46 In the present study, a high density of α-mannose was functionalized on the surface of GNPs, and they appear to work for targeting MR.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In this study, GNPs immobilized with α-mannose were examined for selective delivery of a small molecule TLR7 ligand to immune cells via the MR. A major constraint for targeting CLRs including MR is that their interactions with monovalent sugar-chain structures is quite weak. Multivalent display of sugar chain called “sugar chain cluster effect” are thus crucial for the enhancement of affinity of sugar chains to CLRs. , Our previous studies demonstrated that sugar chain immobilized fluorescent nanoparticles (SFNPs), which are immobilized with a high density of sugar chains on the surface of quantum dots, can selectively bind to cell surface sugar chain binding receptors. , In the present study, a high density of α-mannose was functionalized on the surface of GNPs, and they appear to work for targeting MR.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of 1V209-αFuc-GNPs, 1 , 7 , and tetraethylene glycol (TEG)-mono 10 were coimmobilized onto GNPs at a molar ratio of 1:2.7:6.3, respectively. Because hydrophobicity of fucose is higher than that of the other sugar structures, 10 was immobilized to avoid hydrophobic interactions and aggregation of the particles . Sugar immobilized GNPs (SGNPs) without coimmobilization of 1 were also prepared as control nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…To study the cell binding and internalization properties of nanoparticles coimmobilized with 1V209 and sugar moieties by fluorescence-based flow cytometry analysis, we prepared eight fluorescent nanoparticles coimmobilized 1V209 and sugar moieties (1V209-SFNPs) that immobilized with sugar structures corresponding to 1V209-SGNPs. These particles consisted of CdTe/CdS core/shell quantum dots , and are similar in particle size, immobilization ratios of the compounds, and lectin-binding properties compared to 1V209-SGNPs (SI Table S2 and Figure S8 and S9). To analyze the binding of nanoparticles to the cells, fluorescent dyes are typically conjugated to the nanoparticles; however, the fluorescent property of the dye is likely to be impaired by the conjugation to the GNPs due to the broadband ultraviolet–visible absorption of GNPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation